Multi-attribute temporal descriptive methods in sensory analysis applied in food science: a systematic scoping review - Visalli, Michel (2024)
Fil: Visalli, Michel. Université Bourgogne. Centre des Sciences du Goût et de l’Alimentation. Institut Agro Dijon; Francia